Synthesis of sparse linear array using IFT-inflating deflating exploration algorithm - Guo, Qiang; Liu, Taiyan; Li, Daren; Huang, Shuai; Kaliuzhnyi, Mykola (Digital signal processing, 2025)
In this paper, we propose a new antenna array synthesis algorithm (IFT-IDEA), aimed at synthesizing sparse arrays with low sidelobe levels (SLL) under specified sparsity. The algorithm starts by selecting an initial thinned linear array using Iterative Fourier techniques (IFT). Then, it uses convex optimization to iteratively expand and contract the elements, further optimizing the element excitations and positions to achieve lower sidelobe levels under specified sparsity. During the iterative optimization process, the array's weighted linear density is approximated to a reference value to ensure that all elements are retained. Numerical results demonstrate that IFT-IDEA is effective for synthesizing both symmetric and asymmetric arrays, it also performs well in optimization of large linear array. Additionally, we explored the use of IFT-IDEA for synthesizing low sidelobe patterns with null placement. Compared to other algorithms, IFT-IDEA exhibits superior performance and robustness in the problem of low sidelobe array synthesis.